VICTIM’S RIGHT COMPLIANCE IN DOMESTIC VIOLANCE CASES BASED ON A VICTIMOLOGY PERSPEKTIVE - Ramadiansyah Arie Saputra; Lucky Nurhadiyanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Domestic violence is a serious issue that continues to be a major challenge in Indonesia. In the context of resolving domestic violence conflicts, the fulfillment of victims' rights is a crucial aspect that is often overlooked. Victims' rights such as the right to protection, justice, recovery, and restitution should be prioritized at every stage of the conflict resolution process. The research offers a critical understanding of the gaps between formal legal frameworks and the lived experiences of victims, highlighting the need for a more integrated, victim-centered approach to domestic violence response in Indonesia. The author acknowledges that qualitative research is descriptive in nature and typically uses analytical techniques; the more thorough the analysis, the higher the quality of the research outcomes. This study is linked to Travis Hirschi’s Social Bond Theory, which is suitable for understanding how the rights of domestic violence victims can be fulfilled. This theory posits that the stronger a person’s bonds to others, social values, and positive activities, the less likely they are to commit violations or experience injustice. The results of this study on efforts to fulfill rights in resolving domestic violence conflicts from the victim’s perspective indicate that this issue requires serious attention. Women are highly vulnerable to becoming victims of domestic violence due to their social and cultural positions that place them in a disadvantaged condition, as well as power imbalances within the household.